High-power diode laser for second-stage implant surgery: a randomized pilot clinical trial (Research, Society and Development, 2020)
The present study aimed to compare the conventional scalpel technique and the use of a high-power diode laser for second-stage implant surgery. For that, fifteen patients were randomly assigned to receive either the conventional scalpel technique (Control Group, n = 7) or a diode laser-assisted technique (Laser Group, n = 8) for second-stage surgery of submerged dental implants placed at bone level. The local anesthetic amount required, and the total surgical time was determined just after surgery. Local pain, peri-implant mucosa status, and bleeding were assessed at the end of the surgery and after 7 and 15 days. Information on the need for postoperative pain medication on the first day and during the next two weeks was also gathered. The surgical time was significantly shorter in the Laser Group (P = 0.001) and only the Control Group presented bleeding at the end of surgery and on the seventh day (P =